PEMBERHENTIAN PERANGKAT DESA BERDASARKAN PASAL 53 UNDANGUNDANG NOMOR 6 TAHUN 2014 TENTANG DESA (Studi Kasus Di Desa Begori Kecamatan Serawai Kabupaten Sintang) - Gadion Gadion (PERAHU (PENERANGAN HUKUM) : JURNAL ILMU HUKUM, 2018)
The dismissal of the village apparatus by the Village Head is one of the authority of the Village Head in leading the village area the dismissal must be based on recommendations from the District, one of which is the Camat recommendation letter issued and submitted to the Village Head, the recommendation letter must be based on the submission of the Village Chief by underlying the results of the community election and submission submitted by the Village Head to occupy a position as a Village Tool.